REFLECTIONS ABOUT THE CONCEPTS OF IDENTITY AND DIVERSITY IN THE HISTORY BNCC - Eschriqui Vieira Pinto, Jorge Vieira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2019)
The History is a strategic curricular discipline for any public policies in the area of Education as it is the study of the biographies, actions and cultural heritages of the ancestors, from of the demands of the societies of the present time, able to build a collective memory and to awake in the individuals a symbolic dimension of bond between the present and the past. This bond occurs through comparative approach among several societies in different times, which enables the perception of the permanences and ruptures and, consequently, the understanding of the cultural heritages that approach or distance communities and social groups of the present and of the past, awakening, thus, in the individuals the ties of identity from recognition of the we and differentiation of the other. The purpose of this paper is to analyze how the National Curricular Common Core (BNCC) proposes the pedagogical work with the identity and diversity in History classes.
Keywords: Identity; Diversity; BNCC; History